The Other Worker: A Comparative Study of Industrial Relations in the United States and Japan(Honolulu: East-West Center Press, 1968), 481 pp., $12.50. - Whitehill, Arthur M.; Takezawa, Shin-ichi (Academy of Management Journal, 1969)
The article reviews the book ?The Other Worker: A Comparative Study of Industrial Relations in the United States and Japan,? by Arthur M. Whitehill and Shin-Ichi Takezawa.